PEMANFAATAN SMART TV INTERAKTIF DALAM MENDUKUNG PEMBELAJARAN DI SEKOLAH DASAR - Agustiani, Herlina; Fitria Nurulaeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the use of interactive Smart TVs in supporting learning in elementary schools. The study was motivated by the availability of interactive Smart TVs in schools, whose use in learning has not yet been optimized. The method used was descriptive qualitative research conducted at SDN Cibunar 3 in Sukabumi Regency, with teachers serving as the primary informants. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive analysis model. The results indicate that interactive Smart TVs are used to present various digital learning resources, making learning more engaging, interactive, and easier for students to understand. The use of this medium also increased students’ attention and engagement, although the use of its interactive features was not yet optimal due to teachers’ limited technological proficiency. Thus, interactive Smart TVs support the creation of more effective, interactive, and meaningful learning in elementary schools.